“Strengthening Cyber Policing in India: A Critical Study of The Role and Reform of the Indian Cyber Crime Coordination Centre (I4c)” - Goyal, Himani Raj (Journal of Neonatal Surgery, 2025)
The escalation of cybercrime in India has necessitated the creation of a unified enforcement framework capable of responding to the complex, borderless nature of digital offences. This research critically examines the Indian Cyber Crime Coordination Centre (I4C) as a central institutional response to this challenge. Through an eight-chapter structure, the study maps the legal foundation, functional architecture, and operational impact of I4C in reshaping India’s cybercrime enforcement paradigm. The paper begins by tracing the evolution of cyber enforcement policy in India and the institutional vacuum that preceded I4C. It then provides a functional analysis of I4C’s multi-tiered components such as the National Cybercrime Reporting Portal (NCRP), National Cybercrime Threat Analytics Unit (NCTAU), and National Cybercrime Training Centre (NCTC) and how they enable intelligence-led policing. A dedicated chapter explores institutional challenges, including the absence of statutory authority, inconsistent state cooperation, and capacity deficits at grassroots levels. The study also benchmarks I4C against global best practices from jurisdictions such as the United States (IC3) and Singapore (CSA), exposing gaps in legislative autonomy and international cooperation. The research further incorporates landmark case studies including Operation Chakra, the Chinese Loan App Scam, and coordinated phishing crackdowns to assess I4C’s practical efficacy. A full before-and-after analysis establishes how I4C has transitioned India from fragmented, reactive enforcement to a centralised, predictive model. The final chapter proposes legal and policy reforms, including the need for statutory recognition, harmonised cyber SOPs, and deeper public-private cooperation. This study justifies each research objective by offering a doctrinal and empirical evaluation of I4C as a transformative but evolving institution in India’s digital criminal justice framework. It contributes original academic value by bridging theoretical, comparative, and operational analyses of cyber enforcement in the Indian context.